Knowledge and Acceptability of HIV pre-exposure prophylaxis (PrEP) among men who have sex with men (MSM) in Ghana. Issue 3 (3rd March 2020) - Ogunbajo, Adedotun; Leblanc, Natalie M.; Kushwaha, Sameer; Boakye, Francis; Hanson, Samuel; Smith, Martez D.R.; Nelson, LaRon E.
ABSTRACT: In Ghana, men who have sex with men (MSM) are disproportionately affected by HIV. Pre-exposure prophylaxis (PrEP) is a biomedical intervention that reduces the risk of HIV infection but is not currently available in Ghana. This paper explores knowledge and acceptability of HIV PrEP among Ghanaian MSM. Qualitative content analysis was conducted on 22 focus group discussions ( N  = 137) conducted between March and June 2012 in Accra, Kumasi, and Manya Krobo. Overall, participants reported low knowledge of PrEP. However, once information about PrEP was provided, there was high acceptability. The primary reason for acceptability was that PrEP provided an extra level of protection against HIV. Acceptability of PrEP was conditioned on it having minimal side effects, being affordable and efficient in preventing HIV infection. No acceptability of PrEP was attributed to limited knowledge of side effects and perceived lack of effectiveness. The reasons provided to utilize PrEP and condoms were that condoms protect against other STIs, and sexual partner factors. This is the first known study to explore PrEP knowledge and acceptability among Ghanaian MSM. It is important that key stakeholders preemptively address potential barriers to PrEP acceptability, uptake, and adherence, especially among MSM, once PrEP becomes available in Ghana.